EFEKTIVITAS PEMBELAJARAN MEMBACA AL-QUR’AN PADA ANAK USIA 5-6 TAHUN DENGAN MENGGUNAKAN METODE TILAWATI BERIRAMA DI TPQ NURUS SALAM SERAH GRESIK - Safitri, Linda Afiya; Ulum, Mohammad Samsul (Jurnal Penelitian Anak Usia Dini, 2024)
The tilawati method studied by the author is said to be rhythmic, because the tilawati method at TPQ Nurus Salam uses 4 songs that are appropriate for its class. This research method uses a quantitative approach with an experimental research type. The research design uses one group pre-test post-test. The population in this study were all volume 4 aged 5-6 years at TPQ Nurus Salam Serah Gresik. The data collection techniques used were observation and student learning outcome tests. Data collected through tests and described using the Paired Sample T-test hypothesis test. The results of the study showed that (1) The implementation of the rhythmic tilawati method volume 4 at TPQ Nurus Salam was always carried out by teachers which included a classical approach using teaching aids, teachers exemplified rhythmic reading on the teaching aids, carried out an individual approach with the reading and listening technique, and carried out daily evaluations. This is proven by an average score of 3.66. (2) Measuring the effectiveness of learning the Qur'an using the rhythmic tilawati method at TPQ Nurus Salam using Pre-Test Post-Test, in this measurement it shows that, after implementing the rhythmic tilawati method at TPQ Nurus Salam it has an influence on the development of reading the Qur'an of children aged 5-6 years. It can be seen from the increase in the average value from the pre-test 70.0 to the post-test 87.5.